Health-seeking behaviors during an outbreak of acute conjunctivitis in Central India - Samrat Chatterjee; Anil B Gangwe; Deepshikha Agrawal (Indian Journal of Ophthalmology)
Purpose: To report the health-seeking behaviors of individuals with acute viral conjunctivitis during an outbreak. Methods: A cross-sectional survey was carried out in the Raipur district of Chhattisgarh after an outbreak of acute conjunctivitis in July–August 2023. Results: The treatment choices were pharmacies (51.4%), ophthalmologists (21.1%), quacks (non-qualified doctors) (6.8%), general practitioners (1.6%), home remedies (5.2%), and no treatment (13.9%). Treatment preferences were influenced by place of residence (P < 0.001), occupation (P = 0.002), socioeconomic category (P < 0.001), and highest level of education of male (P < 0.001) and female (P < 0.001) members within the household. The overall expenditure was higher when patients sought treatment from quacks (INR 427.27 ± 202.21), followed by ophthalmologists (INR 374.57 ± 251.31) and pharmacies (INR 201.39 ± 102.65) (P < 0.001). Individuals aged 21–40 years (odds ratio [OR]: 0.24, 95% CI: 0.05–1.03, P = 0.055) and those from villages (OR: 0.16, 95% CI: 0.07–0.32, P < 0.001) were less likely to use prophylaxis. Individuals from families with high level of education of male members (OR: 2.70, 95% CI: 1.08–7.20, P = 0.039) or large family sizes (OR: 6.27, 95% CI: 2.42–19.09, P = 0.039) were more likely to use prophylaxis. The use of separate items of daily use reduced the risk of spread of conjunctivitis (OR: 0.24; 95% CI: 0.06–0.35, P = 0.035). Conclusion: Several insights into health-seeking behaviors among individuals with conjunctivitis during an outbreak were identified in this study, which can aid public health interventions during future outbreaks.